Integrasi-Interkoneksi Ilmu Perspektif Tafsir Sosial TAM (Tuhan Alam dan Manusia) - Imron Muttaqin (AT-TURATS, 2014)
As a great project, the integration and the inter-connection knowledge need a complex system include philosophy that combine the substantive and position of God (meta-cosmos), macro-cosmos (Nature), and micro-cosmos (The human). The knowledge dichotomy in Islam must be reunited by integration and inter-connection, but that efforts need setting of the mindset to avoid an error logical thinking of understanding about substantive, position and goal. The Social Tafseer TAM (God, Nature and Human) is one of alternative way to build the Islamic true logical thinking because it has many purposes in finding Allah`s blessing and also a systematic characteristic in the processes.